बुन्देली वैवाहिक गीत - Gupta, Sudha (Aadivasi Lok Kala evm Boli Vikas Academy Madhya Pradesh Sanskriti Parishad, 2004)
The book is a collection of ritual songs sung on marriage occasions in the area of Bundelkhand.
Bundeli Vaivahik Geet
Keywords: Folk Culture; Hindi; Bundeli